Kajian Putusan Pengadilan tentang Status Anak Akibat Pembatalan Perkawinan No: 740/Pdt.G/2020/Pa.Kng : Komparasi antara Kompilasi Hukum Islam dan Hukum Positif - Alfan Syafi'i; Anni Yunita Safitri (Program Studi Hukum Keluarga (Ahwal Syakhshiyah), 2023)
The status of children is an urgent and serious problem in life in society. In addition to having direct contact with lineage, inheritance, even the matter of guardianship if the child is a girl. In the decision on case Number 740/Pdt.G/2020/PA.Kng, the researcher found that there was no decision regarding the child. This study aims to determine the status of the child as a result of marriage annulment and to find out a comparison between the Compilation of Islamic Law (KHI) and Positive Law in cases of annulment. marriage at the Kuningan Religious Court Number 740/Pdt.G/2020/PA.Kng. The research method used by researchers is qualitative research by combining two types of data, namely data obtained from field research in the form of interviews and documentation at the Kuningan Religious Court and supplemented by library research data in the form of a judge's determination document regarding the case. The data that the researchers obtained were then reduced, presented, and concluded using descriptive-comparative analysis techniques. Based on the research conducted, a conclusion was obtained that the status of a child due to the annulment of a marriage in decision number 740/Pdt.G/2020/PA.Kng is an illegitimate child because he was born in an illegitimate marriage, but regarding civil relations it can be related to his biological father.